Essentials of business law - MacIntyre, Ewan. (Harlow : Pearson Longman, 2007)
This is specifically designed to equip non-law students with an understanding of the essential topics in a business law course. Providing a highly readable explanation of the law, it brings the subject to life through the use of diagrams and examples highlighting how the law operates in its business context.
The legal system -- Making a contract -- The terms of the contract -- Misrepresentation, Mistake, Duress and Illegality -- Discharge of contracts and remedies for breach -- Agency -- The Sale of Goods Act 1979 -- The tort of negligence -- Nuisance, Trespass, Defamation and Vicarious Liability -- Companies (1): Characteristics and formation -- Companies (2): Management, control and winding up -- Partnership, limited liability partnership and choice of legal status -- Employment (1): The contract of employment, employment rights and dismissal -- Employment (2): Discrimination and Health and Safety -- Regulation of business by the criminal law -- Credit transactions and intellectual property rights -- The resolution of business disputes
Includes index.
1
Keywords: Business law -- England; Business law -- Wales